HBsAg e Anti-HBs presentes simultaneamente em uma população especifica de portadores do vírus da Hepatite B - ALBUQUERQUE, Ingrid de Campos (2016)
INTRODUCTION: The concomitant presence of HBsAg and anti-HBs in hepatitis B virus (HBV) infections mainly results from isolated mutations in the a-determinant, which causes changes HBsAg antigenicity. This in turn causes variants unsusceptible to the neutralizing action of anti-HBs, thus permitting immune escape. Therefore, this study had the aim of identifying subjects with this profile among HBsAg carriers identified in an HBV prevalence study. METHODS: The study included participants enrolled in a study of viral hepatitis prevalence from the state of Maranhão in northeastern Brazil. These participants had tested positive for HBsAg and anti-HBs and had quantified HBV DNA. All samples were evaluated for HBsAg, anti-HBs, and anti-HBc. Mutations were sought in the a-determinant located in the S gene s major hydrophilic region (MHR). RESULTS: Among the 3,987 individuals evaluated, 92 (2.3%) were HBsAg carriers. Among these, three had the atypical HBsAg and anti-HBs-positive profile (3.26%). All were identified as subgenotype D4. Only one individual had two S gene mutations, within the a-determinant (Y134N/T140I). CONCLUSION: The frequency of individuals concomitantly positive for HbsAg and anti-HBs was low in the patient sample. Only one individual had mutations in the S gene a-determinant, which is known to be associated with this profile. Nevertheless, the existence of immune escape in communities can have great importance, especially for evaluating immunization programs.